H∞ Control of Networked Control System With Data Packet Dropout via Observer-Based Controller - Yanfeng Wang; Ping He; Heng Li; Xiaoyue Sun; Haoyang Mi; Wei Wei; Xingzhong Xiong; Yangmin Li (IEEE Access, 2020)
The H∞ control problem for networked control system with data packet dropout in both S-C link and C-A link via observer-based controller is researched in this paper. Firstly, the networked control system with data packet dropout in both S-C link and C-A link is modeled as a discrete Markov jump linear system. Secondly, the sufficient and necessary conditions on the stochastic stability of the closed-loop system is established, the solution method of the controller and observer gain matrix are also given on condition that the transition probability matrix is completely known and partly unknown, respectively. The minimal disturbance suppression performance index is also obtained. Finally, two simulation examples illustrate the validity of the proposed method.